Ownership structure and earnings quality pre- and post-IFRS: does investor protection matter? - Abd Alhadi, Saleh; Senik, Rosmila; Johari, Jalila; Nahar, Hairul Suhaimi (University of Malaya, 2020)
Research aims: This study examines whether managerial and institu-tional ownership is associated with higher earnings quality (EQ) after the implementation of International Financial Reporting Standards (IFRS), in comparison to the pre-IFRS period. It also examines the moderating effect of investor protection (INPT) on the link between ownership structure and EQ. Design/Methodology/Approach: This study uses a dynamic panel data modelling on a sample of 2090 firm-year observations, from 2007–2016, in Malaysia. This study applies the generalized method of moments (GMM) to deal with the econometric problems. Research findings: The results indicate that managerial ownership is essential for improving EQ before and after IFRS adoption. No significant improvement is noted for institutional shareholders. The results provide evidence showing that managerial ownership is more efficient in monitoring earnings management in a healthy INPT environment. Theoretical contribution/Originality: The findings highlight the complementary influence of firm- and country-level governance mechanisms in improving firm’s EQ. The results suggest that the agency theory and the institutional theory could be used together in emerging economies. This is because even good CG cannot improve the monitoring performance in countries with weak institutional settings. Practitioner/Policy implication: The results highlight the significance of accounting standards and law enforcement for enhancing the monitoring role of ownership structure in improving EQ. Research limitation/Implications: This study investigates the impact of ownership structure on EQ. Further research should seek to under-stand other CG variables used in other countries with other EQ proxies such as real earnings management.